State regulation of agriculture in modern realities (Journal of Economic Research & Business Administration, 2016)
The agriculture is one of the branches of the economy ensuring activity of society and food security of the state regulated by the state. Accession to WTO needs an increase of competitiveness of agricultural production, introduction of innovations for the purpose of indicators’ increase of pro-ductivity in plant growing, efficiency of animal husbandry which are im-possible without the strongest support from the state increases. A number of measures for strengthening of the state support of agriculture are offered in the article on the basis of the analysis of scientific articles and the avail-able practical development.
Keywords: agro-industrial complex; state regulation; innovative de-velopment; agriculture